Integration of Asma’ul Husna values into industrial designers’ practice - Norzaman, Nor Ziratul Aqma (2022)
Asma’ul Husna embodies the concept of tauhid in Islam. It is a specific way to remember Allah, promote spiritual and moral enhancement, as well as foster excellent quality of ummah. Unfortunately, there are very few studies available on the implementation of Asma’ul Husna in human life, especially in the field of design, and its application has not been fully explored. The findings from the survey conducted serve as proof that the majority of Muslim industrial designers have not adopted Asma’ul Husna into their design practice due to limited knowledge of the ways to integrate Asma’ul Husna into their design process. The Prophet Muhammad s.a.w encouraged Muslims to imitate the moral attributes of Allah, as reflected in Asma’ul Husna, and apply them in life. Thus, it is necessary to provide guidelines for designers to integrate Asma’ul Husna values into their design process, so that designer attitudes and behaviours will always be line with Islamic ethical values. Designers play a big role in determining what to design and manufacture. Based on the literature review conducted, Asma’ul Husna values can help designers to have strong ethical abstraction abilities, be responsible for every decision, and be able to differentiate right from wrong. This study intends to offer a notion of placing Allah at the centre of their work and maximizing Islamic values through the integration of Asma’ul Husna into the design practice. The research consisted of extensive sequential mixed methods including semi-structured interviews, focus group discussions, and a survey. Face-to-face interviews were conducted among Islamic scholars to examine the relevance of Asma’ul Husna, and discover their views regarding the integration of Asma’ul Husna into design practice. Findings from the thematic analysis in Atlas T.I identified correct ways to use Asma’ul Husna and highlight the gap of the study. This is followed by focus group discussions among industrial designers and industrial design academicians based in Malaysia. With the assistance of experts in Asma’ul Husna, the KJ Method was utilised to match Asma’ul Husna with design terminologies and to provide ways for designers to integrate Asma’ul Husna in the design practice. The empirical keywords gained from the focus group discussion were used as the variables to be measured in a survey. A survey conducted among designers and final-year students of industrial design sought to identify the most significant characteristics of an excellent designer, based on designer’s point of view. It also analysed the construct validity and measure the model fit of the Designer Value Framework using SEM Amos. The findings suggest that excellent designers should use Designer Value framework in the early stages of the design process in order to become respectful, virtuous and civilised Muslim designers. It will form alternative guidelines for Muslim designers seeking wealth and practising worldly endeavours, while also desiring to build excellent religious and spiritual characteristics through the integration of Asma’ul Husna values into designers’ practice.